Faktor yang Berhubungan dengan Kejadian Hipertensi pada Ibu Hamil di Rumah Sakit Labuang Baji Makassar - Wahdaniyah (Nutrition Science and Health Research, 2022)
Hypertension is a state of a person's blood pressure that is higher than normal. Hypertension is defined as an increase in systolic pressure of at least 30 mmHg, or diastolic pressure of at least 5 mmHg, or systolic pressure to approximately 140 mmHg, or diastolic to the lowest of 90 mmHg. In developed countries, hypertension of pregnant women is the cause of maternal death, but deaths from hypertension are 150/100,000 births. This study aims to determine the relationship between maternal age, gestational age, antenatal care, parity with the incidence of hypertension in pregnant women at the Labuang Baji Regional General Hospital, Makassar City in 2010. This type of research is Analytical with a Cross Sectional Study Approach. Sampling of 47 pregnant women. The data collection method uses interview methods and questionnaires as research instruments. The results of statistical analysis showed that there was a relationship between maternal age and the incidence of hypertension in pregnant women with a value of x² count (16.027) > x² table (3.841), there was a relationship of gestational age with the incidence of hypertension in pregnant women with a value of x² count (11.153) > x² table (3.841), there was a relationship of Antenatal Care with the incidence of hypertension in pregnant women with a value of x² count (11.153) > x² table (3.841), there was an association of parity with the incidence of hypertension in pregnant women with a value of x² count (10.447) > x² table (3.841). The results of this study are suggested so that mothers can manage their pregnancy, namely in productive age, utilizing antenatal services and having parity in accordance with healthy reproduction.